2008
DOI: 10.1200/jco.2008.17.3526
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hepatitis B Virus and Pancreatic Cancer

Abstract: Purpose Hepatitis B virus (HBV) and hepatitis C virus (HCV) are considered to be hepatotropic and are a major cause of hepatocellular carcinoma. However, little is known about the role of HBV and HCV infection in other malignancies. This study aimed to determine whether HBV and HCV infection increase the risk for pancreatic cancer development. Patients and Methods At The University of Texas M.D. Anderson Cancer Center, Houston, we recruited 476 patients with pathologically confirmed adenocarcinoma of the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(169 citation statements)
references
References 76 publications
4
158
1
6
Order By: Relevance
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…After review, two studies were excluded with the following reasons: a study of HCV infection (El-Serag et al, 2009); a case report (Yoo et al, 2009). Thus, eight articles met the inclusion criteria (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), six of these studies were conducted only in East Asia (de Gonzalez et al, 2008;Iloeje et al, 2009;Hong et al, 2010;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012) and two in USA (Hassan et al, 2008;Gordon et al, 2009).…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
“…There were a total of 302420 individuals in the included eight studies. In most of the studies (de Gonzalez et al, 2008;Hassan et al, 2008;Gordon et al, 2009;Zhu et al, 2011;Ben et al, 2012;Wang et al, 2012), pancreatic cancer was diagnosed according the histology. In other studies (Iloeje et al, 2009;Hong et al, 2010), pancreatic cancer is confirmed by histology or diagnosed by symptoms, signs and more than two types of imaging tools.…”
Section: Literature Search and Studies Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations